No association between ACTN3 R577X Polymorphism and Elite Judo Athletic Status - Rodriguez-Romo, G.; Yvert, T.; de Diego, A.; Santiago, C.; Diaz de Durana, A. L.; Carratala, V.; Garatachea, N.; Lucia, A. (International Journal of Sports Physiology and Performance, 2013)
The authors compared ACTN3 R577X genotype and allele frequencies in the majority of all-time-best Span- ish judo male athletes (n = 108) and 343 ethnically matched nonathletic men. No between-groups differences were found in allele (P = .077) or genotype distributions (P = .178). Thus, the R577X polymorphism was not significantly associated with the status of being an elite judo athlete, at least in the Spanish population. The contribution of genetics to sports-related phenotype traits is undeniable with some genotypes, of which ACTN3 R577X is currently the leading candidate, partly distinguishing individuals predisposed to either endurance or power sports. However, few athletic events can be categorized as purely power or endurance based. Although genetic testing (ie, for ACTN3 R577X) is already being marketed to predict sports talent and potential of young children, its usefulness is still questionable, at least in competitive judo.